Maternal and neonatal outcomes in women with severe early onset pre‐eclampsia before 26 weeks of gestation, a case series. (27th January 2017) - van Oostwaard, MF; van Eerden, L; de Laat, MW; Duvekot, JJ; Erwich, JJHM; Bloemenkamp, KWM; Bolte, AC; Bosma, JPF; Koenen, SV; Kornelisse, RF; Rethans, B; van Runnard Heimel, P; et al.
Abstract : Objective: To describe the maternal and neonatal outcomes and prolongation of pregnancies with severe early onset pre‐eclampsia before 26 weeks of gestation. Design: Nationwide case series. Setting: All Dutch tertiary perinatal care centres. Population: All women diagnosed with severe pre‐eclampsia who delivered between 22 and 26 weeks of gestation in a tertiary perinatal care centre in the Netherlands, between 2008 and 2014. Methods: Women were identified through computerised hospital databases. Data were collected from medical records. Main outcome measures: Maternal complications [HELLP (haemolysis, elevated liver enzyme levels, and low platelet levels) syndrome, eclampsia, pulmonary oedema, cerebrovascular incidents, hepatic capsular rupture, placenta abruption, renal failure, and maternal death], neonatal survival and complications (intraventricular haemorrhage, retinopathy of prematurity, necrotising enterocolitis, bronchopulmonary dysplasia, and sepsis), and outcome of subsequent pregnancies (recurrent pre‐eclampsia, premature delivery, and neonatal survival). Results: We studied 133 women, delivering 140 children. Maternal complications occurred frequently (54%). Deterioration of HELLP syndrome during expectant care occurred in 48%, after 4 days. Median prolongation was 5 days (range: 0–25 days). Neonatal survival was poor (19%), and was worse (6.6%) if the mother was admitted before 24 weeks of gestation. Complications occurred frequently among survivors (84%). After active support, neonatal survival was comparable with the survival of spontaneous premature neonates (54%). Pre‐eclampsia recurred in 31%, at a mean gestational age of 32 weeks and 6 days. Conclusions: Considering the limits of prolongation, women need to be counselled carefully, weighing the high risk for maternal complications versus limited neonatal survival and/or extreme prematurity and its sequelae. The positive prospects regarding maternal and neonatal outcome in future pregnancies can supplement counselling. Tweetable abstract: Severe early onset pre‐eclampsia comes with high maternal complication rates and poor neonatal survival. Tweetable abstract: Severe early onset pre‐eclampsia comes with high maternal complication rates and poor neonatal survival.